An efficient three-dimensional indoor visible light positioning algorithm using multiple transmitters and single receiver - Ummea Afroza (Elsevier, 2021)
Indoor visible light positioning system has received much attention in recent years due to the simultaneous operation of optical wireless communication and object tracking. Here, a 3D positioning algorithm is proposed using multiple transmitters and single receiver. The algorithm is based on dividing the 3D space in several 2D planes along the room height maintaining small resolution and further compute the received signal acts as a reference power for each of the 3D coordinates. By keeping such reference power, the algorithm continues the operation to search for receiver’s unknown 3D position based on the best match of power levels within the set tolerance value. The investigation results show that the average positioning error is 0.658 cm at 3 m height considering a standard room dimension. Moreover, the proposed algorithm is also used for trajectory tracking of a random curve, where around 92% of the positioning error is maintained below 2.7 cm. By knowing the geometry of a room with static setup of transmitters, the proposed algorithm is easy to implement and converge within a short time to get the receiver’s unknown position in 3D space.